Design and In-silico study of bioimaging fluorescence Graphene quantum dot-Bovine serum albumin complex synthesized by diimide-activated amidation. (August 2021) - Patel, Vimal; Shah, Jigar; Gupta, Ajay Kumar
Graphical abstract: GQD tethered BSA complex by carbodiimide amidation and characterization. Highlights: 2D-GQD prepared from pyrolysis of citric acid through bottom-up technique exhibit excitation-dependent fluorescence emission. Narrow size distribution of about 20 nm has been confirmed by AFM and TEM. EDC/NHS diimide activated amidation has created a covalent amide bridge between the BSA and GQD. MD simulation reveals higher negative energy comprises during the interaction make rapid and stable protein-ligand complex. Spectro-fluorescence and virtual screening analysis reveal that GQD-BSA interaction has avoided fluorescence quenching. Abstract: Graphene quantum dot possesses advantageous characteristics like tunable fluorescence, nanometer size, low cytotoxicity, high biocompatibility enabling them as an ideal material for fluorescence bio-imaging. It exhibits a unique characteristic of DNA cleavage activity enhancer, gene/drug carrier, and anticancer targeting applications. In this article, we discussed the preparation of graphene quantum dot through the bottom-up method. Carbodiimide-activated amidation reactions were used for the functionalization of graphene quantum dot with Bovine Serum Albumin. Fluorescence spectroscopy data showed that the graphene quantum dot has size-dependent fluorescence emission. TEM and AFM studies showed that the size of graphene quantum dot was around 20 nm with narrow size distribution. Carbodiimide-activated amidation conjugation was successful in binding the protein onto graphene quantum dot and these conjugates were characterized by DLS, FTIR, fluorescence spectroscopy, and agarose gel electrophoresis. We also studied the structural-based in-silico molecular dynamic simulation by AutoDock, PyRx, and Discovery Studio Visualizer. Based on the virtual screening analysis and higher negative energy incorporation, it is observed that graphene quantum dot conjugated with bovine serum albumin quickly and formed is highly stable complex, which makes them a potential candidate for future applications in the field of bio-imaging, bio-sensing, gene/drug delivery, and tumor theragnostic.